Exposure to an enriched environment promotes dendritic remodelling in hippocampal neurons affected by endogenous depression (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Neuronal plasticity is enhanced in an enriched environment (EE) with more sensory and social interaction. In an animal model of endogenous depression, we have previously shown that EE has positive effects on spatial memory and hippocampus synaptic plasticity. However, nothing is known about how EE influences dendritic remodelling in hippocampal neurons affected by endogenous depression. In depressed rats, the impact of EE on hippocampus neuronal morphology was examined. Neonatal clomipramine exposure from postnatal days (PND) 8-21 days induced endogenous depression. The depressed-like rats were exposed to an enriched environment for two weeks in adulthood. Brains were then collected, stained with a modified Golgi-cox technique and, the hippocampal CA1 dendritic arborisation was evaluated using the Neurolucida software. Depression resulted in the atrophy of CA1 hippocampal neurons. The number of branching points and the overall number of dendritic intersections were reduced in depressed rats,. Exposure to an enriched environment significantly increased dendritic branching and the total number of dendritic intersections in hippocampal CA1 pyramidal neurons. The hippocampal pyramidal neuronal morphology of depressed rats improved after exposure to environmental enrichment. Neuronal plasticity and the development of novel therapeutic strategy will be improved by a greater understanding of how the environment affects neuronal morphology in depressed states.